A modified hollow fiber membrane and its preparation method and application

Through the membrane extraction process of modified hollow fiber membranes, the problems of high ammonia content and high operating costs in the gas are solved, and the continuous and stable removal of ammonia in the gas and the regeneration of water washing water are achieved, which reduces the consumption of water and acid and increases the consumption of water and acid. Deammonia effect.

CN115957640BActive Publication Date: 2025-01-03CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202111178063.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-10-09
Publication Date
2025-01-03
Estimated Expiration
2041-10-09

AI Technical Summary

Technical Problem

In the prior art, the ammonia content in the gas is high, the continuous removal is difficult, and the operating cost is high. The direct contact of the acid liquid with the gas leads to greater water and acid consumption.

Method used

Using a modified hollow fiber membrane, the continuous and stable removal of ammonia-containing gas is achieved through the combination of the base film, graft layer and polydimethylsiloxane layer. The membrane extraction process is used to penetrate ammonia from the water washing solution. Re-extract the lean liquid to avoid direct contact between the washing medium and the ammonia re-extract the lean liquid to reduce water and acid consumption.

Benefits of technology

The continuous and stable removal of ammonia in the gas is achieved, which reduces operating costs, reduces water and acid consumption, improves the deamination effect, and avoids contamination of the water washing system and the back extraction system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115957640B_ABST
    Figure CN115957640B_ABST
Patent Text Reader

Abstract

The present invention discloses a modified hollow fiber membrane and a preparation method and application thereof. The modified hollow fiber membrane comprises a base membrane, a graft layer and an outer wall, wherein the base membrane has a carboxyl content of 3.8 to 11.2 mmol / g and a sulfonic acid content of 1.9 to 8.4 mmol / g; the graft layer has a carboxyl content of 14.4 to 32.4 mmol / g and a sulfonic acid content of 7.2 to 24.3 mmol / g; and the outer wall is a polydimethylsiloxane layer with a thickness of 80 to 160 microns. The modified hollow fiber membrane of the present invention can realize continuous and stable removal of ammonia impurities in gas, reducing the impact of ammonia impurities on subsequent processes or the environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of gas purification, and particularly to a modified hollow fiber membrane and a preparation method thereof, as well as application of the modified hollow fiber membrane in continuously removing trace ammonia from gas. Background Art

[0002] Refinery gas refers to various gases produced as byproducts of petroleum processing, including thermal cracking, catalytic cracking, coking gas and reforming gas. Coke oven gas is a byproduct of coking production. In a coking furnace, coal is heated to a high temperature and distilled to produce gas in an isolated environment. Producer gas is a gas obtained by gasifying coal or coke in a gasifier. According to different gasifiers, it can be divided into air gas, air-steam gas, water gas, double water gas, semi-water gas, etc. Heavy oil cracking gas is water gas or gas produced by thermal cracking gasification using heavy oil as raw material. Anaerobic fermentation gas of organic matter includes biogas produced by fermentation and digestion of garbage. During the generation process of this type of gas, due to the decomposition of nitrogen-containing components in petroleum and coal and proteins in organic matter, the above-mentioned gas contains a small amount of ammonia impurities.

[0003] During the subsequent processing or combustion of the above gases, the ammonia in the gas will cause the activity of the acid catalyst involved in the subsequent process to decrease, or there will be a strong ammonia smell when it is burned. There are many methods for removing ammonia impurities, such as adsorption method and acid absorption method.

[0004] CN108502965A discloses a method for removing ammonia nitrogen from wastewater by zeolite adsorption, wherein the wastewater containing ammonia nitrogen flows through an adsorption device filled with zeolite for adsorption and denitrification treatment, and the adsorption-saturated zeolite material is regenerated by the method of "alkali solution reverse circulation + air blowing + steam stripping", and the regenerated alkali solution is recycled as alkali water for high-ammonia nitrogen wastewater stripping treatment device. In this adsorption method, the zeolite adsorbent is easy to saturate and the regeneration operation is frequent.

[0005] "A Brief Analysis of Coal Gas Deammoniation Technology in Circulating Fluidized Bed Gasifier" (Nonferrous Metals Design, Vol. 46, No. 2, June 2019) introduces three processes for removing and recovering ammonia from coal gas: water-washed ammonia process, ammonium sulfate process, and anhydrous ammonia process. 1) Water-washed ammonia process: This process has a simple process and relatively low investment, but there are problems such as large amount of wastewater produced by water-washed ammonia, complex ammonia evaporation process system, and great impact of ammonia on the environment. 2) Ammonium sulfate process: This process is relatively complex (referring to the complexity of ammonia recovery). It uses sulfuric acid to absorb ammonia in coal gas, reacts ammonia and sulfuric acid to form ammonium sulfate, and achieves natural crystallization by controlling the absorption temperature. Since the process uses corrosion-resistant materials (316L for stationary equipment and 904 for running equipment), although the deammoniation effect is good, the cost of the device is relatively high. 3) Anhydrous ammonia process: The anhydrous ammonia process is the most complex, and ammonia recovery uses a 1.6MPa pressurized ammonia evaporation process, which has high requirements for operating technology, equipment and control systems.

[0006] At present, some methods use modified activated carbon to adsorb ammonia in dry gas. Since the ammonia content in dry gas is unstable, it generally fluctuates greatly between 1 and 500 ppm. When the ammonia content is high, the adsorbent is easily saturated, resulting in frequent loading and unloading of the adsorbent.

[0007] CN111450662A discloses a combined deammoniation process of a water washing tower, a cyclone separator, a coalescer and an adsorption tower, wherein the water washing liquid is selected from industrial water or an acidic aqueous solution, and the adsorbent is formed activated carbon, silicon dioxide, aluminum oxide, formed molecular sieve and strongly acidic cation exchange resin loaded with inorganic acid or organic acid, etc. In this process, since the operation flexibility of the water washing distillation tower is limited, it is difficult to effectively remove ammonia from the refinery gas when the ammonia content in the refinery gas fluctuates greatly. Even if an adsorption tower is set up later, the adsorbent in the adsorption tower is quickly saturated due to the excessive ammonia content in the dry gas.

[0008] The article "Study on Absorption of Ammonia in Phosphate Fertilizer Tail Gas by Rotating Packed Bed" (Chemical Intermediates, Issue 7, 2009) discloses a process for absorbing ammonia in phosphate fertilizer tail gas by using phosphoric acid wastewater. Compared with traditional tower equipment, the absorption efficiency of this process is improved to a certain extent, but the deammoniation effect is average.

[0009] In summary, the existing technology of deammoniation generally uses adsorbents or acid liquid to directly contact the ammonia-containing gas, and has the disadvantages of low operational flexibility and general removal effect. In particular, after the ammonia impurities in the gas are reduced to a certain level, it is more difficult to remove, and the subsequent processing technology or emissions are affected to a certain extent. At the same time, since the acid liquid directly contacts and continuously replaces the ammonia in the gas, it leads to high water and acid consumption. Summary of the invention

[0010] The technical problem to be solved by the present invention is that the ammonia content in the gas is high, the continuous removal is difficult, the operation cost is high, and the like in the prior art. A modified hollow fiber membrane and a preparation method thereof as well as an application in the continuous removal of ammonia in the gas are provided. The modified hollow fiber membrane of the present invention can realize the continuous and stable removal of ammonia impurities in the gas, and reduce the impact of ammonia impurities on subsequent processes or the environment.

[0011] The first aspect of the present invention provides a modified hollow fiber membrane, wherein the modified hollow fiber membrane comprises a base membrane, a grafted layer and an outer wall, wherein the base membrane has a carboxyl content of 3.8 to 11.2 mmol / g and a sulfonic acid content of 1.9 to 8.4 mmol / g; the grafted layer has a carboxyl content of 14.4 to 32.4 mmol / g and a sulfonic acid content of 7.2 to 24.3 mmol / g; and the outer wall is a polydimethylsiloxane layer with a thickness of 80 to 160 microns.

[0012] In the above technical solution, the grafted layer is covered on the inner surface of the base film, and the outer wall is covered on the outer surface of the base film.

[0013] In the above technical solution, the carboxyl content and sulfonic acid content in the base membrane and the carboxyl content and sulfonic acid content in the graft layer are based on per gram of modified hollow fiber membrane.

[0014] In the above technical solution, preferably, the inner diameter of the modified hollow fiber is 0.3 to 1.0 mm.

[0015] In the above technical solution, preferably, in the modified hollow fiber, the base membrane thickness is 0.4 to 1.5 mm, preferably 0.5 to 1.2 mm.

[0016] In the above technical solution, the viscosity of the polydimethylsiloxane is 5000 to 10000 centipoise.

[0017] In the above technical solution, the base film is a polypropylene film modified by a first modifier. The first modifier is sodium poly(4-styrenesulfonic acid-co-maleic acid) and sodium polyanisyl sulfonate, and the mass fraction ratio of sodium poly(4-styrenesulfonic acid-co-maleic acid) to sodium polyanisyl sulfonate is (8-15):(2-6). The sodium poly(4-styrenesulfonic acid-co-maleic acid) is an equimolar copolymer of styrenesulfonic acid and maleic acid, with a molecular weight of 4000-7000, and the molecular weight of sodium polyanisyl sulfonate is 6000-10000. The molecular weight of the polypropylene is 40000-50000.

[0018] A second aspect of the present invention provides a method for preparing a modified hollow fiber membrane, comprising:

[0019] (1) preparing a basement membrane;

[0020] (2) coating the inner surface of the base film with a grafted layer;

[0021] (3) Then, the outer surface of the base membrane is covered with an outer wall to obtain a modified hollow fiber membrane.

[0022] In the above technical solution, preferably, the process of preparing the base membrane in step (1) comprises: preparing a casting liquid containing a first modifier, a core liquid and an outer gel bath, and then forming the hollow fiber membrane by hollow fiber spinning and drying to obtain a hollow fiber membrane, namely the base membrane.

[0023] In the above technical solution, preferably, the process of coating the graft layer on the inner surface of the base membrane in step (2) comprises: swelling the hollow fiber membrane, treating it with a second modifier, and treating it with a third modifier to coat the graft layer.

[0024] In the above technical solution, preferably, the process of covering the outer surface of the base membrane with an outer wall in step (3) comprises: performing a third modification post-treatment on the hollow fiber membrane covered with a grafted layer obtained in step (2) to cover it with a polydimethylsiloxane layer to obtain a modified hollow fiber membrane.

[0025] In the above technical solution, the first modifier described in step (1) is sodium poly(4-styrenesulfonic acid-co-maleic acid) and sodium polyanisyl sulfonate, and the mass ratio of sodium poly(4-styrenesulfonic acid-co-maleic acid) to sodium polyanisyl sulfonate is (8-15):(2-6). Wherein, sodium poly(4-styrenesulfonic acid-co-maleic acid) is an equimolar copolymer of styrenesulfonic acid and maleic acid, with a molecular weight of 4000-7000, and the molecular weight of sodium polyanisyl sulfonate is 6000-10000.

[0026] In the above technical scheme, the casting solution containing the first modifier in step (1) includes: polypropylene (molecular weight of 40,000 to 50,000), N-methylpyrrolidone, diethylene glycol, and the first modifier, wherein the mass ratio of polypropylene, N-methylpyrrolidone, diethylene glycol, and the first modifier is (20 to 30): (100 to 150): (2 to 6): (10 to 20). The preparation method of the casting solution containing the first modifier includes: stirring and mixing polypropylene, N-methylpyrrolidone, diethylene glycol, and the first modifier at 80 to 120° C. for 24 to 48 hours, and then standing and degassing for 5 to 10 hours to obtain the casting solution containing the first modifier. The core liquid is an N-methylpyrrolidone solution, wherein the mass concentration of the N-methylpyrrolidone solution is 2% to 8%. The outer gel bath is desalted water.

[0027] In the above technical scheme, the hollow fiber membrane molding described in step (1) can be obtained by a conventional spinning method. Among them, the spinning conditions are preferably as follows: the inner diameter and outer diameter of the spinneret are adjusted according to the inner diameter of the hollow fiber membrane and the thickness of the base membrane, the temperature of the core liquid and the outer gel bath is 0-3°C, the air gap height is 2-4 cm, the fiber collection rate is free fall, the flow rate of the casting liquid is 7-10 ml / min, the pressure of the casting liquid in the spinneret is 100-300 kPa (gauge pressure), the flow rate of the core liquid is 3-7 ml / min, the ambient temperature is 20-30°C, the ambient humidity is 50%-70%, and the casting liquid containing the first modifier undergoes solvent exchange with the core liquid and the outer gel bath and solidifies in phase separation to form a hollow fiber membrane blank. The hollow fiber embryos are washed with desalted water 4 to 8 times, low carbon alcohols (such as methanol and / or ethanol) 4 to 8 times, and n-hexane 4 to 8 times, and then dried in an inert atmosphere (such as nitrogen) at 20 to 30° C. to obtain hollow fiber membranes.

[0028] In the above technical scheme, the swelling agent used in step (2) is selected from at least one of toluene, p-xylene, m-xylene, and o-xylene, the swelling temperature is 80-120°C, the swelling time is 5-12 hours, and the volume ratio of the swelling agent to the hollow fiber membrane is 2-5.

[0029] In the above technical scheme, the second modifier described in step (2) is a second modifying component (the second modifying component is selected from at least one of 1,3,5-tris[4-(chloromethyl)phenyl]benzene, 1,3,5-trichlorobenzene, and 1,3,5-tris(chloromethyl)benzene), a catalyst and a solvent; the catalyst is selected from one of a Lewis acid or a Lewis base, preferably at least one of anhydrous zinc chloride, anhydrous tin tetrachloride, and anhydrous aluminum chloride; the solvent is selected from at least one of toluene, p-xylene, m-xylene, and o-xylene; in terms of mass fractions, the second modifying component: catalyst: solvent = (5-15): (1-3): (100-200).

[0030] In the above technical solution, the treatment conditions of the second modifier are as follows: the second modifier passes through the inner cavity of the hollow fiber membrane, the flow line speed is 0.2 m / s to 0.5 m / s, the treatment temperature is 30° C. to 60° C., and the treatment time is 20 to 40 minutes. After the hollow fiber membrane is treated with the second modifier, a modified hollow fiber membrane intermediate is obtained.

[0031] In the above technical scheme, the modified hollow fiber membrane intermediate is subjected to a third modification treatment and a third modification post-treatment to obtain a modified hollow fiber membrane. The third modifier is a third modification component (the third modification component is selected from at least one of N-(carboxymethyl) maleamic acid, 3,4,5-tricarboxylic acid aniline, and 5-(3,5-dicarboxybenzamide)isophthalic acid), sodium hydroxide and a solvent; the solvent is selected from at least one of toluene, p-xylene, m-xylene, and o-xylene; by mass, the third modification component: sodium hydroxide: solvent = (5-15): (1-3): (100-200).

[0032] In the above technical solution, the treatment conditions of the third modifier treatment are as follows: the third modifier passes through the inner cavity of the hollow fiber membrane, the flow line velocity is 0.2 m / s to 0.5 m / s, the treatment temperature is 40°C to 80°C, and the treatment time is 5 to 15 minutes.

[0033] In the above technical solution, the post-treatment agent used in the third modification post-treatment is a polydimethylsiloxane solution, and the solvent is selected from at least one of toluene, p-xylene, m-xylene, and o-xylene. The mass concentration of the polydimethylsiloxane solution is 2% to 6%. The outer wall of the modified hollow fiber membrane obtained by the third modification post-treatment is coated with polydimethylsiloxane with a thickness of 80 to 160 microns. The third post-modification treatment includes: dip coating the outer wall of the hollow fiber membrane with a polydimethylsiloxane solution with a mass concentration of 2% to 6%, the dip coating time is 2 to 7 seconds, and then drying in a vacuum drying oven at 50°C to 70°C, the pressure (absolute pressure) of the vacuum drying oven is 50 to 80 kPa, and the drying time is 4 to 8 hours; then soaking with a low-carbon alcohol (the low-carbon alcohol is selected from at least one of methanol and ethanol) at a soaking temperature of 40°C to 60°C, 1 to 5 times, and each soaking time is 1 to 3 hours; then soaking with an acid aqueous solution with a mass concentration of 1% to 5% (the acid is selected from at least one of sulfuric acid, hydrochloric acid, and phosphoric acid), the soaking temperature is 40°C to 60°C, the soaking time is 1 to 5 times, and each soaking time is 1 to 3 hours, and the acid aqueous solution is rinsed with desalted water to neutrality after soaking. Wherein, the viscosity of polydimethylsiloxane is 5000 to 10000 centipoise.

[0034] The third aspect of the present invention provides a modified hollow fiber membrane prepared by the above method.

[0035] In the above technical scheme, the modified hollow fiber membrane includes a base membrane, a grafted layer and an outer wall, wherein the carboxyl content in the base membrane is 3.8 to 11.2 mmol / g, and the sulfonic acid content is 1.9 to 8.4 mmol / g; the carboxyl content in the grafted layer is 14.4 to 32.4 mmol / g, and the sulfonic acid content is 7.2 to 24.3 mmol / gram; the outer wall is covered with polydimethylsiloxane with a thickness of 80 to 160 microns.

[0036] In the above technical solution, the grafted layer is covered on the inner surface of the base film, and the outer wall is covered on the outer surface of the base film.

[0037] In the above technical solution, the carboxyl content and sulfonic acid content in the base membrane and the carboxyl content and sulfonic acid content in the graft layer are based on per gram of modified hollow fiber membrane.

[0038] In the above technical solution, the inner diameter of the modified hollow fiber is 0.3 to 1.0 mm.

[0039] In the above technical solution, in the modified hollow fiber, the base membrane thickness is 0.4 to 1.5 mm, preferably 0.5 to 1.2 mm.

[0040] The fourth aspect of the present invention provides use of the modified hollow fiber membrane described in the first aspect or the modified hollow fiber membrane described in the third aspect in a process for deammoniation of ammonia-containing gas.

[0041] In the above technical solution, the gas may be derived from at least one of ammonia-containing gases such as refinery gas, coke oven gas, biogas, biomass gasification gas, water gas, and garbage anaerobic digestion gas.

[0042] In the above technical solution, the deamination process is a water-washing deamination process, and the application is to use the modified hollow fiber membrane as a membrane extraction component to perform back extraction on ammonia-containing water washing liquid.

[0043] A fifth aspect of the present invention provides a method for continuously removing ammonia from an ammonia-containing gas, comprising:

[0044] S1, the raw gas is washed with water to remove ammonia impurities through a water washing tower, and ammonia-containing water washing liquid is obtained at the top of the tower;

[0045] S2, stripping the ammonia-containing water washing liquid using a membrane extraction assembly having the modified hollow fiber membrane, wherein the ammonia-containing water washing liquid and the ammonia stripping lean solution flow through the inner cavity and outer wall of the modified hollow fiber membrane respectively to obtain a deammoniation water washing liquid and an ammonia stripping rich solution;

[0046] S3, the ammonia stripping rich solution is degraded by electro-oxidation to obtain a regenerated ammonia stripping lean solution.

[0047] In the above technical solution, the regenerated ammonia stripping lean liquid described in step S3 can be recycled as ammonia stripping lean liquid in step S2.

[0048] In the above technical solution, the deammoniation washing liquid described in step S2 can be recycled as the washing medium of the washing tower in step S1.

[0049] In the above technical scheme, the ammonia-containing washing liquid obtained in step S1 is pre-treated before step S2, and the pre-treatment is to filter the ammonia-containing washing liquid using a security filter. The security filter is a bag-type and / or folding filter with a filtration accuracy of 3 to 10 microns. The filtration temperature is 10 to 40°C, and the filtration pressure is 0.5 to 1.0 MPaG.

[0050] In the above technical scheme, in step S1, the raw gas is derived from ammonia-containing gas, such as at least one of refinery gas, coke oven gas, biogas, biomass gasification gas, water gas, and garbage anaerobic digestion gas. The raw gas includes, but is not limited to, ethylene, methane, ethane, propane, propylene, isobutane, n-butane, trans-butene, n-butene, isobutene, cis-butene, oxygen, nitrogen, hydrogen, carbon monoxide, carbon dioxide, acetylene, 1,3-butadiene, at least one of alkanes or alkenes with a carbon content of more than five, and also includes ammonia impurities. The ammonia impurities in the raw gas have a volume content of not less than 100ppm, preferably not less than 600ppm, more preferably not less than 1000ppm, and further, the volume content is not higher than 2000ppm.

[0051] In the above technical solution, in step S1, the water washing tower can be a conventional plate tower or packed tower in the art. The water washing medium and the raw gas are in countercurrent contact in the tower body.

[0052] In the above technical scheme, in step S1, the number of theoretical plates of the water washing tower is 3 to 8, the water washing temperature is 10 to 40°C, and the water washing pressure is 0.5 to 1.0 MPaG. The water washing medium is industrial fresh water, desalted water, or sodium chloride aqueous solution, preferably sodium chloride aqueous solution. The mass concentration of the sodium chloride aqueous solution is 0.1% to 2.0%. The usage ratio of the raw gas to the water washing medium is, by volume, 50 to 80.

[0053] In the above technical scheme, in step S2, the interior of the membrane extraction component is filled with the modified hollow fiber membrane, and the ammonia in the ammonia-containing water washing liquid is permeated and extracted through the modified hollow fiber membrane to reach the outside of the modified hollow fiber membrane, and mass transfer is achieved with the ammonia stripping lean liquid under the promotion of the concentration gradient, and finally the ammonia in the ammonia-containing water washing liquid is transferred to the ammonia stripping lean liquid, so that the ammonia-containing water washing liquid can be continuously deammonified and regenerated.

[0054] In the above technical solution, in step S2, the ammonia stripping lean solution is industrial fresh water, desalted water or sodium chloride aqueous solution. The mass concentration of the sodium chloride aqueous solution is 100-500 ppm.

[0055] In the above technical solution, in step S1, the feed rate of raw gas to the water scrubber is 10000~50000Nm 3In step S2, the filling amount of the modified hollow fiber membrane regular module is 30-40m 3 The cross-sectional arrangement density of the modified hollow fiber membrane in the modified hollow fiber membrane regular module is 30,000 to 60,000 pieces / m 2 .

[0056] In the above technical solution, in step S2, the temperature at which the ammonia-containing washing liquid contacts the modified hollow fiber membrane is 20-50° C. and the pressure is 0.5-1.0 MPaG.

[0057] In the above technical solution, in step S2, the temperature at which the ammonia stripping lean solution contacts the modified hollow fiber membrane is 20-50° C. and the pressure is 0.5-1.0 MPaG.

[0058] In the above technical solution, in step S2, the ammonia-containing washing liquid and the ammonia stripping lean liquid are in a volume ratio of ammonia-containing washing liquid: ammonia stripping lean liquid = 1: (2 to 6).

[0059] In the above technical solution, in step S3, the ammonia stripping rich solution is degraded by electro-oxidation to obtain a regenerated ammonia stripping lean solution. The mass content of chlorine in the regenerated ammonia stripping lean solution is controlled to be less than 1 ppm (preferably less than 0.5 ppm), and the mass content of ammonia is controlled to be less than 3 ppm. The regenerated ammonia stripping lean solution in step S3 can be recycled as the ammonia stripping lean solution in step S2.

[0060] In the above technical solution, in step S3, the electro-oxidation uses a titanium-based coating electrode modified with tin, antimony or copper.

[0061] The method for preparing the titanium-based coating electrode modified with tin, antimony and copper comprises:

[0062] Step I, pretreatment of the titanium plate substrate: polishing the titanium plate substrate with 30-50 mesh white corundum in turn, soaking in a sodium hydroxide aqueous solution with a mass concentration of 30%-40% at 50-80° C. for 1-2 hours, rinsing with desalted water to neutrality, soaking in a sulfuric acid aqueous solution with a mass concentration of 20%-30% at 50-80° C. for 1-2 hours, rinsing with desalted water to neutrality, and storing in a nitrogen atmosphere to obtain a pretreated titanium plate substrate;

[0063] Step II, preparing a coating dipping solution: first, citric acid and ethylene glycol are mixed in a molar ratio of 1:(3-6), and reacted at 60-90° C. for 1-2 hours to obtain a citrate ethylene glycol solution; then, the citrate ethylene glycol solution, tin chloride pentahydrate, antimony trichloride, and copper nitrate trihydrate are mixed in a mass ratio of 1000:(94-98):(2-6):(0.5-2) for 0.5-1.0 hours to obtain a coating dipping solution;

[0064] Step III, scraping 200 to 300 ml per square meter of titanium plate substrate, scraping in an inert atmosphere (such as nitrogen) to obtain a scraping wet plate; drying at 100 to 150 kPaG and 120 to 150° C. for 0.5 to 1.0 hour under an inert atmosphere (such as nitrogen) to obtain a scraping dry substrate;

[0065] Step IV, the above-mentioned scraping dried substrate is roasted in an air roasting furnace at 100-150 kPaG and 500-550° C. for 10-30 minutes to obtain a scraping roasted substrate;

[0066] Step V, repeat steps III and IV 10 to 15 times, and the last calcination conditions are as follows: calcination in an air calcination furnace at 100 to 150 kPaG, 500 to 550°C, for 1 to 2 hours to obtain a titanium-based coating electrode modified with tin, antimony and copper.

[0067] In the above technical solution, in step S3, the electro-oxidation preferably adopts a multi-stage electro-oxidation reactor, further a two-stage to six-stage electro-oxidation reactor, such as a three-stage electro-oxidation reactor, i.e., a first-stage electro-oxidation reactor, a second-stage electro-oxidation reactor, and a third-stage electro-oxidation reactor, and the electrode size in the electro-oxidation reactor is (2-3 meters) × (4-6 meters), and the electrode spacing is 1-3 centimeters. The cathode of the electro-oxidation reactor is a titanium mesh, and the anode is the titanium-based coating electrode modified with tin, antimony, and copper.

[0068] In the above technical solution, in step S3, the electrolyte of the electro-oxidation reactor has a mass concentration of sodium sulfate and sodium chloride of 3% to 6% and 0.1% to 4% respectively, and the rest is desalted water. The linear velocity of the electrolyte on the electrode surface is 0.3 to 0.7 m / s.

[0069] In the above technical solution, in step S3, the electro-oxidation reaction conditions are as follows: voltage of 1.2 to 1.6 V, current density of 7 to 50 mA / cm2, operating pressure of 0.5 to 1.0 MPaG, and operating temperature of 20 to 40° C. Preferably, when a multi-stage electro-oxidation reactor is used, an electro-oxidation reactor with a stepwise decreasing current density is used.

[0070] In the above technical solution, in step S3, taking a three-stage electro-oxidation reactor as an example, the electro-oxidation reaction conditions are as follows:

[0071] The first-stage electro-oxidation reactor has a voltage of 1.2 to 1.6 volts, a current density of 30 to 50 mA / cm2, an operating pressure of 0.5 to 1.0 MPaG, and an operating temperature of 20 to 40°C;

[0072] The second-stage electro-oxidation reactor has a voltage of 1.2 to 1.6 V, a current density of 15 to 25 mA / cm2, an operating pressure of 0.5 to 1.0 MPaG, and an operating temperature of 20 to 40°C;

[0073] The third-stage electro-oxidation reactor has a voltage of 1.2 to 1.6 V, a current density of 7 to 12 mA / cm2, an operating pressure of 0.5 to 1.0 MPaG, and an operating temperature of 20 to 40°C.

[0074] In the above technical solution, the volume content of ammonia in the deammoniation washing liquid obtained in step S2 is not higher than 10 ppm.

[0075] In the above technical solution, the volume content of ammonia in the deammonification purified gas obtained in step S1 is not higher than 5 ppm, preferably not higher than 3 ppm.

[0076] In the above technical solution, the deammoniation purified gas obtained in step S1 can meet the requirements of subsequent processing sections or environmental emissions.

[0077] A fifth aspect of the present invention provides a separation system for continuously and stably removing ammonia from gas, comprising:

[0078] 1) Water scrubber, used to remove ammonia impurities in the raw gas;

[0079] 2) A membrane extraction component, used to extract and remove ammonia impurities from the ammonia-containing washing solution and transfer the mass to the ammonia stripping lean solution;

[0080] 3) Electro-oxidation reactor, used for oxidative removal of ammonia impurities in ammonia stripping rich liquid.

[0081] Compared with the prior art, the present invention has the following advantages:

[0082] 1. The inventor of the present invention has found through research that during the deep processing or domestic combustion of raw gas (such as refinery gas, coke oven gas, biogas, biomass gasification gas, water gas, and garbage anaerobic digestion gas), the ammonia impurities present in the raw gas will be adsorbed on the active center of the catalyst used in the deep processing process, resulting in the catalyst activity and product selectivity being affected; or there will be ammonia smell during the combustion process, causing environmental pollution. Due to the volatility of nitrogen-containing components of coal, petroleum, and solid waste and processing or fermentation processes, the ammonia impurities in the raw gas continue to fluctuate significantly. If only conventional adsorbents (such as ion exchange resins, activated carbon, zeolites, etc.) are used for fixed bed adsorption, the adsorbent is easily saturated, conventional regeneration operations are frequent, and the amount of wastewater discharged is large. If a water scrubber is directly used to wash water for deammoniation, in order to ensure the deammoniation effect, the consumption of fresh water is extremely large and the cost is high. If sulfuric acid aqueous solution is used for deammoniation, the equipment material requirements are high and the equipment investment is large. At the same time, since the deammoniation agent (such as acid water) is directly in contact with the ammonia in the gas for deammoniation and discharge, recycling is not achieved, and the water consumption is too large. Furthermore, the degradation rate of ammonia by direct oxidation reaction of hydroxyl radicals is slow. Although ammonia in aqueous solution can be removed by indirect electro-oxidation reaction by adding sodium chloride salt, chlorine gas will be produced due to electrolysis reaction during the indirect electro-oxidation reaction. If chlorine-containing water is used in a water scrubber, the chlorine in the washing water will be decomposed into the raw gas during the washing and ammonia removal process, resulting in "chlorine poisoning" of the catalyst in the subsequent processing technology. In some working conditions, the raw gas contains a certain amount of reducing gas (such as hydrogen). When the strong oxidant produced by the indirect electro-oxidation reaction is in direct contact with the reducing gas, there is a safety hazard. Therefore, the electro-oxidation method cannot be directly used for the regeneration of the washing liquid medium. The inventors have found through further research that the modified hollow fiber membrane of the present invention is used for membrane extraction process through the modified base membrane containing sulfonic acid groups and carboxyl groups, the grafted layer containing carboxyl groups and sulfonic acid groups, and the matching of the hydrophobic dense outer wall with a certain degree of polymerization, which can not only realize the high rate and high selectivity of the membrane to absorb ammonia in the ammonia-containing water washing liquid, but also realize the penetration of the ammonia component into the ammonia stripping lean liquid driven by the concentration difference, while avoiding the contact between the washing medium and the ammonia stripping lean liquid logistics, and the washing medium after deammoniation is returned to the washing tower for recycling, so as to achieve the effect of deammoniation close to fresh water; the ammonia stripping lean liquid logistics isolated from the washing water circulation system can be conveniently processed in depth, and at the same time, it does not cause pollution to the washing water circulation system or raw gas. Preferably, multi-stage electro-oxidation is adopted, and by controlling the operating parameters and sodium chloride concentration of the electro-oxidation reactor, the ammonia in the ammonia stripping rich liquid is effectively removed, the ammonia stripping rich liquid is regenerated, and the residual chlorine in the ammonia stripping lean liquid is reduced, the influence of the residual chlorine on the hollow fiber membrane structure is reduced, and the service life of the hollow fiber membrane is maintained.

[0083] 2. The present invention solves the problems in the prior art of high ammonia content in the gas, great difficulty in continuous removal, high operating cost, and many impurities in the crystalline product caused by direct contact of the acid solution, and realizes the continuous purification and regeneration of the washing water and the continuous purification and regeneration of the stripping solution. At the same time, a selective permeable dense layer is used to isolate the raw gas washing system from the ammonia impurity stripping system in the washing water, and the ammonia in the stripping system can be electro-oxidized and degraded into nitrogen. BRIEF DESCRIPTION OF THE DRAWINGS

[0084] Figure 1 This is a schematic diagram of a separation system for continuously and stably removing ammonia from gas according to the present invention;

[0085] The reference numerals are described as follows:

[0086] 101 is a water washing tower, 102 is a security filter, 103 is a membrane extraction component, 104 is an ammonia stripping rich liquid buffer tank, 105 is an electrolyte delivery pump, 106 is a first-stage electro-oxidation reactor, 107 is a second-stage electro-oxidation reactor, 108 is a third-stage electro-oxidation reactor, 109 is an ammonia stripping lean liquid buffer tank, 110 is an ammonia stripping lean liquid delivery pump, 201 is a raw gas inlet, 202 is a deammoniation purified gas outlet, 203 is a fresh water washing medium replenishment port, 204 is a fresh electrolyte replenishment port, and 205 is an electrolyte discharge port. DETAILED DESCRIPTION

[0087] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the protection scope of the present invention.

[0088] In the present invention, the analysis of low-carbon hydrocarbon components and ammonia is performed by gas chromatography Agilent 7890A GC (Agilent, USA), equipped with a HP-PLOT Al2O3 KCl (50m×0.53mm×15μm) capillary column, the column temperature is maintained at 100°C for 10 minutes, then increased to 120°C at 30°C per minute, and maintained for 3 minutes. The carrier gas He flow rate is 3mL / min, the injection volume is 0.1mL (quantitative loop), the split ratio is 5:1, the injection port temperature is 250°C, and the detector (FID) temperature is 250°C.

[0089] A separation system for continuously and stably removing ammonia from gas according to the present invention (such as Figure 1As shown), it includes: 101 is a water scrubber, 102 is a security filter, 103 is a membrane extraction component, 104 is an ammonia stripping rich liquid buffer tank, 105 is an electrolyte delivery pump, 106 is a first-stage electro-oxidation reactor, 107 is a second-stage electro-oxidation reactor, 108 is a third-stage electro-oxidation reactor, 109 is an ammonia stripping lean liquid buffer tank, and 110 is an ammonia stripping lean liquid delivery pump. The separation process is as follows: the raw gas 201 (for example, from refinery gas, coke oven gas, biogas, biomass gasification gas, water gas, and garbage anaerobic digestion gas) enters the lower part of the water scrubber 101, and contacts with the water scrubbing medium coming from the upper part of the water scrubber 101 in the tower body in countercurrent flow, and the ammonia impurities in the raw gas are separated and removed. The deammoniation purified gas 202 after deammonification enters the subsequent unit. The ammonia-containing washing liquid in the water washing tower kettle is filtered through the security filter 102 and then enters the membrane extraction component 103 for regeneration. In the membrane extraction component, the ammonia-containing washing liquid passes through the inner cavity of the modified hollow fiber membrane, and the ammonia back-extraction lean liquid passes through the outer wall of the modified hollow fiber membrane. The deammoniation water washing tower washing medium after deammoniation is mixed with part of the fresh water washing medium replenished from the fresh water washing medium replenishing port 203 and then returned to the water washing tower 101 for recycling. The ammonia stripping rich liquid after extracting ammonia from the ammonia-containing washing medium enters the ammonia stripping rich liquid buffer tank 104, and part of the fresh electrolyte replenished from the fresh electrolyte replenishing port 204 is mixed with the ammonia stripping rich liquid, and then transported to the upper or lower part of the first-stage electro-oxidation reactor 106 through the electrolyte delivery pump 105 for primary oxidation, and then flows by gravity to the upper or lower part of the second-stage electro-oxidation reactor 107 for secondary oxidation, and then flows by gravity to the upper or lower part of the third-stage electro-oxidation reactor 108 for tertiary oxidation. The oxidation product of the third-stage electro-oxidation reactor 108 enters the ammonia stripping lean liquid buffer tank 109, and is transported to the electrolyte discharge port 205 through the ammonia stripping lean liquid delivery pump 110 to discharge part of the electrolyte, and then transported to the membrane extraction component 103.

[0090] [Example 1]

[0091] The raw gas described in this embodiment is derived from refinery gas, and its composition by volume ratio includes: methane 18.7322%, ethane 8.5285%, ethylene 15.8432%, propane 0.1788%, propylene 0.8635%, isobutane 0.0831%, normal butane 0.0164%, trans-butene 0.0070%, normal butene 0.0195%, isobutene 0.0381%, cis-butene 0.0002%, oxygen 0.1329%, nitrogen 13.1458%, hydrogen 28.4233%, carbon monoxide 1.5636%, carbon dioxide 3.4974%, acetylene 0.0056%, 1,3-butadiene 0.0001%, hydrogen sulfide 6.6454%, C5 or above alkanes or alkenes 1.2569%, ammonia 0.0560%, and other components 0.9627%.

[0092] The separation process of this embodiment is the same as Figure 1 As shown, the method for continuously and stably removing ammonia from refinery gas comprises:

[0093] S1) the raw gas is passed through a water scrubber to remove ammonia impurities, a deammoniation purified gas is obtained at the top of the tower, and an ammonia-containing water washing liquid is obtained at the bottom of the tower;

[0094] S2) the ammonia-containing washing liquid is filtered through a security filter to obtain a pre-treated ammonia-containing washing liquid; the pre-treated ammonia-containing washing liquid is passed through the inner cavity of the modified hollow fiber membrane of the membrane extraction component to obtain a deammoniation washing liquid; the deammoniation washing liquid is continuously used in step S1; the ammonia stripping lean liquid is transferred with the pre-treated ammonia-containing washing liquid through the modified hollow fiber membrane in the shell side of the membrane extraction component to obtain an ammonia stripping rich liquid;

[0095] S3) The ammonia stripping rich liquid is oxidized and degraded step by step in the electro-oxidation reactor to obtain an ammonia stripping lean liquid; the ammonia stripping lean liquid is continuously used in step S2.

[0096] The water washing tower is a plate tower. The water washing medium and the raw gas are in countercurrent contact in the tower body. The theoretical number of plates of the water washing tower is 6, the water washing temperature is 25°C, and the water washing pressure is 0.7MPaG. The water washing medium is a sodium chloride aqueous solution, and the mass concentration of the sodium chloride aqueous solution is 1%. The dosage ratio of the raw gas to the water washing medium is, by volume, 65.

[0097] The security filter is a bag filter with a filtration accuracy of 5 microns. The filtration temperature is 25°C and the filtration pressure is 0.7MPaG.

[0098] The interior of the membrane extraction component is filled with a modified hollow fiber membrane, through which ammonia in the pretreated ammonia-containing water washing liquid is infiltrated and extracted to reach the outside of the modified hollow fiber membrane, and then mass transfer is achieved with the ammonia stripping lean liquid under the promotion of the concentration gradient, and finally ammonia in the pretreated ammonia-containing water washing liquid is transferred to the ammonia stripping lean liquid, so that the pretreated ammonia-containing water washing liquid can be continuously deaminated and regenerated.

[0099] The preparation method of the modified hollow fiber membrane comprises: preparing a casting solution containing a first modifier, a core solution and an outer gel bath, and then forming and drying the hollow fiber membrane by hollow fiber spinning. Then, the hollow fiber membrane is swollen, treated with a second modifier, treated with a third modifier and post-modification treatment to obtain a modified hollow fiber membrane.

[0100] The first modifier is sodium poly(4-styrenesulfonic acid-co-maleic acid) (molecular weight 5500) and sodium polyanisyl sulfonate (molecular weight 8000), and the mass ratio of sodium poly(4-styrenesulfonic acid-co-maleic acid) to sodium polyanisyl sulfonate is 11:4. The preparation conditions of the hollow fiber membrane are as follows: polypropylene (molecular weight 45000), N-methylpyrrolidone, diethylene glycol, and the first modifier are in a mass ratio of 25:125:4:15, stirred at 100°C for 36 hours, and then allowed to stand for degassing for 7 hours to obtain a casting solution containing the first modifier. The core liquid composition is N-methylpyrrolidone: water = 5:95 in a mass ratio. The outer gel bath composition is desalted water. The inner diameter of the spinneret is 0.6 mm, the outer diameter is 2.4 mm, the temperature of the core liquid and the outer gel bath is 2°C, the air gap height is 3 cm, the collection rate is free fall, the casting liquid flow rate is 8.5 ml / min, the casting liquid pressure in the spinneret is 200 kPa (gauge pressure), the core liquid flow rate is 5 ml / min, the ambient temperature is 25°C, the ambient humidity is 60%, the casting liquid and the core liquid and the outer gel bath undergo solvent exchange and phase separation solidification to form a hollow fiber membrane blank. The hollow fiber blank is washed with desalted water 6 times, methanol 6 times, and n-hexane 6 times, and then dried in a nitrogen atmosphere at 25°C to obtain a hollow fiber membrane.

[0101] The hollow fiber swelling agent was toluene, the swelling temperature was 100° C., the swelling time was 8.5 hours, and the volume ratio of the swelling agent to the hollow fiber membrane was 3.5.

[0102] The second modifier is 1,3,5-trichlorobenzene, anhydrous zinc chloride and toluene, and the mass fraction is 1,3,5-trichlorobenzene: anhydrous zinc chloride: toluene = 10:2:150. The conditions for the second modifier treatment are as follows: the second modifier solution passes through the inner cavity of the hollow fiber membrane, the flow line velocity is 0.35 m / s, the treatment temperature is 45°C, and the treatment time is 30 minutes. After the hollow fiber membrane is treated with the second modifier, a modified hollow fiber membrane intermediate is obtained.

[0103] The modified hollow fiber membrane intermediate is subjected to a third modification treatment and a third modification post-treatment to obtain a modified hollow fiber membrane. The third modifier is 3,4,5-tricarboxylic acid aniline, sodium hydroxide and toluene, and the mass fractions are 3,4,5-tricarboxylic acid aniline: sodium hydroxide: toluene = 10:2:150. The conditions for the third modifier treatment are as follows: the third modifier solution passes through the inner cavity of the hollow fiber membrane, the flow line velocity is 0.35 m / s, the treatment temperature is 60°C, and the treatment time is 10 minutes.

[0104] The third post-modification treatment includes: using a 4% polydimethylsiloxane (viscosity of 7500 centipoise) toluene solution to dip coat the outer wall of the hollow fiber membrane for 4.5 seconds, followed by drying in a 60°C vacuum drying oven with a pressure (absolute pressure) of 65 kPa for 6 hours; followed by immersion in ethanol at a temperature of 50°C, 3 times, and 1.5 hours each time; followed by immersion in a 3% aqueous sulfuric acid solution at a temperature of 50°C, 3 times, and 1.5 hours each time, and rinsing with desalted water to neutrality after immersion in the aqueous sulfuric acid solution.

[0105] The prepared modified hollow fiber membrane has an inner diameter of 0.6 mm, a base membrane thickness of 0.9 mm, a carboxyl content of 7.5 mmol / g, and a sulfonic acid content of 5.1 mmol / g in the base membrane; the carboxyl content of the grafted layer is 23.3 mmol / g, and the sulfonic acid content is 15.6 mmol / g; and the thickness of the outer wall polydimethylsiloxane is 120 microns.

[0106] In step S1, the feed rate of raw gas to the water scrubber is 30000 Nm 3 / hour, the filling capacity of the modified hollow fiber membrane regular module is 35m 3 The cross-sectional arrangement density of the modified hollow fiber membrane in the modified hollow fiber membrane regular module is 45,000 pieces / m 2 . In step S2, the temperature at which the pre-treated ammonia-containing water washing liquid contacts the modified hollow fiber membrane is 35°C and the pressure is 0.7 MPaG. In step S2, the ammonia stripping lean solution is a sodium chloride solution with a mass concentration of 300 ppm. In step S2, the temperature at which the ammonia stripping lean solution contacts the modified hollow fiber membrane is 35°C and the pressure is 0.7 MPaG. In step S2, the ammonia-containing water washing liquid and the ammonia stripping lean solution are in a volume ratio of ammonia-containing water washing liquid: ammonia stripping lean solution = 1:4.

[0107] In step S3, the electro-oxidation reactor is equipped with a titanium-based coating electrode modified by tin, antimony, and copper. The preparation method of the titanium-based coating electrode modified by tin, antimony, and copper includes: step I, pretreatment of the titanium plate substrate, polishing the titanium plate substrate with 40 mesh white corundum in turn, soaking in a sodium hydroxide aqueous solution with a mass concentration of 35% at 65°C for 1.5 hours, rinsing with desalted water to neutrality, soaking in a sulfuric acid aqueous solution with a mass concentration of 25% at 65°C for 1.5 hours, rinsing with desalted water to neutrality, and storing in a nitrogen atmosphere to obtain a pretreated titanium plate substrate. Step II, preparing an immersion solution, first mixing citric acid and ethylene glycol at a molar ratio of 1:4.5, and reacting at 75°C for 1.5 hours to obtain a citrate ethylene glycol solution; then mixing the citrate ethylene glycol solution, tin chloride pentahydrate, antimony trichloride, and copper nitrate trihydrate at a mass ratio of 1000:96:4:1.2 for 0.7 hours to obtain a coating immersion solution. Step III, scrape 250 ml per square meter of titanium plate substrate in a nitrogen atmosphere to obtain a scrape-coated wet plate; the above-mentioned scrape-coated wet plate is dried in a nitrogen drying oven at 125kPaG and 135°C for 0.7 hours to obtain a scrape-coated dry substrate; Step IV, the above-mentioned scrape-coated dry substrate is roasted in an air roasting furnace at 125kPaG and 525°C for 20 minutes, and then naturally cooled to room temperature to obtain a scrape-coated roasted substrate; repeat steps III and IV for 13 times, and the last roasting conditions are as follows: the roasting time is controlled to be 1.5 hours in an air roasting furnace at 125kPaG and 525°C to obtain a titanium-based coating electrode modified with tin, antimony and copper.

[0108] In step S3, the electro-oxidation reactor is composed of a first-stage electro-oxidation reactor, a second-stage electro-oxidation reactor, and a third-stage electro-oxidation reactor. The electrode size in the electro-oxidation reactor is (2.5 meters) × (5 meters), the electrode spacing is 2 centimeters, the cathode is a titanium mesh, and the anode is the above-mentioned titanium-based coating electrode. In step S6, the electrolyte of the electro-oxidation reactor has a mass concentration of sodium sulfate and sodium chloride of 4.5% and 2%, respectively, and the rest is desalted water. The linear velocity of the electrolyte on the electrode surface is 0.5 meters per second. The voltage of the first-stage electro-oxidation reactor is 1.4 volts, the current density is 40 milliamperes per square centimeter, the operating pressure is 0.7 MPaG, and the operating temperature is 30°C. The voltage of the second-stage electro-oxidation reactor is 1.4 volts, the current density is 20 milliamperes per square centimeter, the operating pressure is 0.7 MPaG, and the operating temperature is 30°C. The third-stage electro-oxidation reactor has a voltage of 1.4 V, a current density of 9.5 mA / cm2, an operating pressure of 0.7 MPaG, and an operating temperature of 30° C. The chlorine content in the ammonia stripping lean solution after regeneration reaches 0.5 ppm, and the ammonia content reaches 1.5 ppm.

[0109] The ammonia content in the deammoniation water washing liquid obtained in step S2 is 5ppm. The ammonia content in the deammoniation purified gas obtained in step S1 is 3ppm, which can meet the feed requirements of the subsequent processing technology.

[0110] [Example 2]

[0111] The raw gas described in this embodiment is the same as that in embodiment 1. The separation process of this embodiment is the same as that in embodiment 1.

[0112] The water washing tower is a plate tower. The water washing medium and the raw gas are in countercurrent contact in the tower body. The theoretical number of plates of the water washing tower is 7, the water washing temperature is 15°C, and the water washing pressure is 0.9MPaG. The water washing medium is a sodium chloride aqueous solution, and the mass concentration of the sodium chloride aqueous solution is 1.8%. The dosage ratio of the raw gas to the water washing medium is, by volume, 55.

[0113] The security filter is a bag filter with a filtration accuracy of 5 microns. The filtration temperature is 15°C and the filtration pressure is 0.9MPaG.

[0114] The interior of the membrane extraction component is filled with a modified hollow fiber membrane, through which ammonia in the pretreated ammonia-containing water washing liquid is infiltrated and extracted to reach the outside of the modified hollow fiber membrane, and then mass transfer is achieved with the ammonia stripping lean liquid under the promotion of the concentration gradient, and finally ammonia in the pretreated ammonia-containing water washing liquid is transferred to the ammonia stripping lean liquid, so that the pretreated ammonia-containing water washing liquid can be continuously deaminated and regenerated.

[0115] The preparation method of the modified hollow fiber membrane comprises: preparing a casting solution containing a first modifier, a core solution and an outer gel bath, and then forming and drying the hollow fiber membrane by hollow fiber spinning. Then, the hollow fiber membrane is swollen, treated with a second modifier, treated with a third modifier and post-modification treatment to obtain a modified hollow fiber membrane.

[0116] The first modifier is sodium poly(4-styrenesulfonic acid-co-maleic acid) (polymer molecular weight of 5000) and sodium polyanisyl sulfonate (polymer molecular weight of 7000), and the mass ratio of sodium poly(4-styrenesulfonic acid-co-maleic acid) to sodium polyanisyl sulfonate is 14:3. The preparation conditions of the hollow fiber membrane are as follows: polypropylene (molecular weight of 45000), N-methylpyrrolidone, diethylene glycol, and the first modifier are in a mass ratio of 22:145:5:18, stirred at 110°C for 45 hours, and then allowed to stand for degassing for 9 hours to obtain a casting solution containing the first modifier. The core liquid composition is N-methylpyrrolidone: water = 3:97 by mass ratio. The outer gel bath composition is desalted water. The inner diameter of the spinneret is 0.4 mm, the outer diameter is 2.8 mm, the temperature of the core liquid and the outer gel bath is 0.5°C, the air gap height is 3.5 cm, the collection rate is free fall, the casting liquid flow rate is 7.5 ml / min, the casting liquid pressure in the spinneret is 150 kPa (gauge pressure), the core liquid flow rate is 4 ml / min, the ambient temperature is 23°C, the ambient humidity is 65%, the casting liquid and the core liquid, the outer gel bath undergo solvent exchange and phase solidification to form a hollow fiber membrane blank. The hollow fiber embryo was washed with desalted water 7 times, methanol 7 times, and n-hexane 7 times, and then dried in a nitrogen atmosphere at 22°C to obtain a hollow fiber membrane.

[0117] The hollow fiber swelling agent was toluene, the swelling temperature was 110° C., the swelling time was 11 hours, and the volume ratio of the swelling agent to the hollow fiber membrane was 4.

[0118] The second modifier is 1,3,5-trichlorobenzene, anhydrous zinc chloride and toluene, and the mass fraction is 1,3,5-trichlorobenzene: anhydrous zinc chloride: toluene = 14:2.5:120. The conditions for the second modifier treatment are as follows: the second modifier solution passes through the inner cavity of the hollow fiber membrane, the flow line velocity is 0.25 m / s, the treatment temperature is 55°C, and the treatment time is 35 minutes. After the hollow fiber membrane is treated with the second modifier, a modified hollow fiber membrane intermediate is obtained.

[0119] The modified hollow fiber membrane intermediate is subjected to a third modification treatment and a third modification post-treatment to obtain a modified hollow fiber membrane. The third modifier is 3,4,5-tricarboxylic acid aniline, sodium hydroxide and toluene, and by weight, 3,4,5-tricarboxylic acid aniline: sodium hydroxide: toluene = 14:2.5:115. The conditions for the third modifier treatment are as follows: the third modifier solution passes through the inner cavity of the hollow fiber membrane, the flow line velocity is 0.25 m / s, the treatment temperature is 76°C, and the treatment time is 13 minutes.

[0120] The third post-modification treatment includes: using a 3% polydimethylsiloxane (viscosity of 6000 centipoise) toluene solution to dip coat the outer wall of the hollow fiber membrane for 3 seconds, followed by drying in a 55°C vacuum drying oven with a pressure (absolute pressure) of 75kPa for 7 hours; followed by immersion in ethanol at a temperature of 55°C, 4 immersions, and 2 hours each immersion; followed by immersion in a 4.5% sulfuric acid aqueous solution at a temperature of 55°C, 4 immersions, and 2 hours each immersion, and rinsing with desalted water to neutrality after immersion in the sulfuric acid aqueous solution.

[0121] The prepared modified hollow fiber membrane has an inner diameter of 0.4 mm, a base membrane thickness of 1.2 mm, a carboxyl content of 10.8 mmol / g, and a sulfonic acid content of 7.9 mmol / g in the base membrane; the carboxyl content of the grafted layer is 28.7 mmol / g, and the sulfonic acid content is 22.6 mmol / g; and the thickness of the outer wall polydimethylsiloxane is 90 microns.

[0122] In step S1, the feed rate of raw gas to the water scrubber is 30000 Nm 3 / hour, the filling capacity of the modified hollow fiber membrane regular module is 38m 3 The cross-sectional arrangement density of the modified hollow fiber membrane in the modified hollow fiber membrane regular module is 55,000 pieces / m 2 . In step S2, the ammonia stripping lean solution is a sodium chloride solution with a mass concentration of 400ppm. In step S2, the temperature at which the pretreated ammonia-containing water washing solution and the modified hollow fiber membrane are in contact is 45°C and the pressure is 0.9MPaG. In step S2, the temperature at which the ammonia stripping lean solution and the modified hollow fiber membrane are in contact is 45°C and the pressure is 0.9MPaG. In step S2, the ammonia-containing water washing solution and the ammonia stripping lean solution are in a volume ratio of ammonia-containing water washing solution: ammonia stripping lean solution = 1:5.

[0123] In step S3, the electro-oxidation reactor is equipped with a titanium-based coating electrode modified by tin, antimony, and copper. The preparation conditions of the titanium-based coating electrode modified by tin, antimony, and copper are as follows: Step I, pretreatment of the titanium plate substrate, polishing the titanium plate substrate with 35 mesh white corundum in turn, soaking in a sodium hydroxide aqueous solution with a mass concentration of 38% at 75°C for 1.8 hours, rinsing with desalted water to neutrality, soaking in a sulfuric acid aqueous solution with a mass concentration of 27% at 75°C for 1.8 hours, rinsing with desalted water to neutrality, and storing in a nitrogen atmosphere to obtain a pretreated titanium plate substrate. Step II, preparing an immersion solution, first mixing citric acid and ethylene glycol in a molar ratio of 1:4.0, and reacting at 85°C for 1.7 hours to obtain a citrate ethylene glycol solution; then mixing the citrate ethylene glycol solution, tin chloride pentahydrate, antimony trichloride, and copper nitrate trihydrate, by mass, 1000 parts: (97 parts): (5 parts): (1.7 parts) for 0.9 hours to obtain a coating immersion solution. Step III, apply 290 ml of the scraper coating per square meter of the titanium plate substrate in a nitrogen atmosphere to obtain a scraper-coated wet plate; the above-mentioned scraper-coated wet plate is dried in a nitrogen drying oven at 105 kPaG and 125°C for 0.9 hours to obtain a scraper-coated dry substrate; Step IV, the above-mentioned scraper-coated dry substrate is roasted in an air roasting furnace at 105 kPaG and 545°C for 25 minutes, and then naturally cooled to room temperature to obtain a scraper-coated roasted substrate; repeat steps III and IV for 14 times, and for the last roasting, control the roasting time to be 1.8 hours in an air roasting furnace at 105 kPaG and 545°C to obtain a titanium-based coating electrode modified with tin, antimony and copper.

[0124] In step S3, the electro-oxidation reactor is composed of a first-stage electro-oxidation reactor, a second-stage electro-oxidation reactor, and a third-stage electro-oxidation reactor. The electrode size in the electro-oxidation reactor is (2.8 meters) × (5.7 meters), the electrode spacing is 1.5 centimeters, the cathode is a titanium mesh, and the anode is the above-mentioned titanium-based coating electrode modified with tin, antimony, and copper. The electrolyte of the electro-oxidation reactor, in terms of mass concentration, has a mass concentration of 5.5% and 3% of sodium sulfate and sodium chloride, respectively, and the rest is desalted water. The linear velocity of the electrolyte on the electrode surface is 0.4 meters per second. In step S6, the voltage of the first-stage electro-oxidation reactor is 1.5 volts, the current density is 45 milliamperes per square centimeter, the operating pressure is 0.9 MPaG, and the operating temperature is 35°C. In step S3, the voltage of the second-stage electro-oxidation reactor is 1.5 volts, the current density is 23 milliamperes per square centimeter, the operating pressure is 0.9 MPaG, and the operating temperature is 35°C. In step S3, the voltage of the third-stage electro-oxidation reactor is 1.5 V, the current density is 11 mA / cm2, the operating pressure is 0.9 MPaG, and the operating temperature is 35° C. The chlorine content in the ammonia stripping lean solution after regeneration reaches 0.1 ppm, and the ammonia content reaches 0.9 ppm.

[0125] The ammonia content in the deammoniation washing liquid obtained in step S2 is 3 ppm. The ammonia content in the deammoniation purified gas obtained in step S1 is 1.2 ppm, which can meet the feed requirements of the subsequent processing technology.

[0126] [Example 3]

[0127] The raw gas described in this embodiment is the same as that in embodiment 1. The separation process of this embodiment is the same as that in embodiment 1.

[0128] The water washing tower is a conventional plate tower in the art. The water washing medium and the raw gas are in countercurrent contact in the tower body. The theoretical number of plates of the water washing tower is 4, the water washing temperature is 35°C, and the water washing pressure is 0.6MPaG. The water washing water is a sodium chloride aqueous solution, and the mass concentration of the sodium chloride aqueous solution is 0.5%. The dosage ratio of the raw gas to the water washing medium is, by volume, 75.

[0129] The security filter is a bag filter with a filtration accuracy of 5 microns. The filtration temperature is 35°C and the filtration pressure is 0.6MPaG.

[0130] The interior of the membrane extraction component is filled with a modified hollow fiber membrane, through which ammonia in the pretreated ammonia-containing water washing liquid is infiltrated and extracted to reach the outside of the modified hollow fiber membrane, and then mass transfer is achieved with the ammonia stripping lean liquid under the promotion of the concentration gradient, and finally ammonia in the pretreated ammonia-containing water washing liquid is transferred to the ammonia stripping lean liquid, so that the pretreated ammonia-containing water washing liquid can be continuously deaminated and regenerated.

[0131] The preparation method of the modified hollow fiber membrane comprises: preparing a casting solution containing a first modifier, a core solution and an outer gel bath, and then performing hollow fiber spinning and drying by a conventional method to obtain a hollow fiber membrane. Then, the hollow fiber membrane is swollen, treated with a second modifier, treated with a third modifier and post-modification treatment to obtain a modified hollow fiber membrane.

[0132] The first modifier is sodium poly(4-styrenesulfonic acid-co-maleic acid) (molecular weight 6000) and sodium polyanisyl sulfonate (molecular weight 9000), and the mass ratio of sodium poly(4-styrenesulfonic acid-co-maleic acid) to sodium polyanisyl sulfonate is 9:5. The preparation conditions of the hollow fiber membrane are as follows: polypropylene (molecular weight 45000), N-methylpyrrolidone, diethylene glycol, and the first modifier are in a mass ratio of 28:115:3:12, stirred at 90°C for 30 hours, and then allowed to stand for degassing for 6 hours to obtain a casting solution containing the first modifier. The core liquid composition is N-methylpyrrolidone: water = 7:93 by mass ratio. The outer gel bath composition is desalted water. The inner diameter of the spinneret is 0.9 mm, the outer diameter is 2.3 mm, the temperature of the core liquid and the outer gel bath is 2.5°C, the air gap height is 2.5 cm, the collection rate is free fall, the casting liquid flow rate is 9.5 ml / min, the casting liquid pressure in the spinneret is 250 KPa (gauge pressure), the core liquid flow rate is 6 ml / min, the ambient temperature is 28°C, the ambient humidity is 55%, the casting liquid and the core liquid, the outer gel bath undergo solvent exchange and phase solidification to form a hollow fiber membrane blank. The hollow fiber embryo is washed with desalted water 5 times, methanol 5 times, and n-hexane 5 times, and then dried in a nitrogen atmosphere at 27°C to obtain a hollow fiber membrane.

[0133] The hollow fiber swelling agent is toluene, the swelling temperature is 85° C., the swelling time is 6 hours, and the volume ratio of the swelling agent to the hollow fiber membrane is 3.

[0134] The second modifier is 1,3,5-trichlorobenzene, anhydrous zinc chloride and toluene, and the mass fraction is 1,3,5-trichlorobenzene: anhydrous zinc chloride: toluene = 7:1.5:180. The conditions for the second modifier treatment are as follows: the second modifier solution passes through the inner cavity of the hollow fiber membrane, the flow line velocity is 0.45 m / s, the treatment temperature is 35°C, and the treatment time is 25 minutes. After the hollow fiber membrane is treated with the second modifier, a modified hollow fiber membrane intermediate is obtained.

[0135] The modified hollow fiber membrane intermediate is subjected to a third modification treatment and a third modification post-treatment to obtain a modified hollow fiber membrane. The third modifier is 3,4,5-tricarboxylic acid aniline, sodium hydroxide and toluene, and the mass fractions are 3,4,5-tricarboxylic acid aniline: sodium hydroxide: toluene = 7:1.5:185. The conditions for the third modifier treatment are as follows: the third modifier solution passes through the inner cavity of the hollow fiber membrane, the flow line velocity is 0.45 m / s, the treatment temperature is 45°C, and the treatment time is 6 minutes.

[0136] The third post-modification treatment includes: using a 5% polydimethylsiloxane (viscosity of 9000 centipoise) toluene solution to dip coat the outer wall of the hollow fiber membrane for 6 seconds, followed by drying in a 65°C vacuum drying oven with a pressure (absolute pressure) of 55 kPa for 5 hours; followed by immersion in ethanol at a temperature of 45°C, twice, and each immersion time of 1.2 hours; followed by immersion in a 2% aqueous sulfuric acid solution at a temperature of 45°C, twice, and each immersion time of 1.2 hours, and after immersion in the aqueous sulfuric acid solution, rinse with desalted water until neutral.

[0137] The prepared modified hollow fiber membrane has an inner diameter of 0.9 mm, a base membrane thickness of 0.7 mm, a carboxyl content of 4.3 mmol / g, and a sulfonic acid content of 2.1 mmol / g in the base membrane; the carboxyl content of the grafted layer is 15.4 mmol / g, and the sulfonic acid content is 7.9 mmol / g; and the thickness of the outer wall polydimethylsiloxane is 140 microns.

[0138] In step S1, the feed rate of raw gas to the water scrubber is 40000 Nm 3 / hour, the filling capacity of the modified hollow fiber membrane regular module is 32m 3 The cross-sectional arrangement density of the modified hollow fiber membrane in the modified hollow fiber membrane regular module is 40,000 pieces / m 2 . In step S2, the ammonia stripping lean solution is a sodium chloride solution with a mass concentration of 200 ppm. In step S2, the temperature at which the pretreated ammonia-containing water washing solution and the modified hollow fiber membrane are in contact is 25°C and the pressure is 0.6 MPaG. In step S2, the temperature at which the ammonia stripping lean solution and the modified hollow fiber membrane are in contact is 25°C and the pressure is 0.6 MPaG. In step S2, the ammonia-containing water washing solution and the ammonia stripping lean solution are in a volume ratio of ammonia-containing water washing solution: ammonia stripping lean solution = 1:3.

[0139] In step S3, the electro-oxidation reactor is equipped with a titanium-based coating electrode modified by tin, antimony, and copper. The preparation method of the titanium-based coating electrode modified by tin, antimony, and copper comprises: step I, pretreatment of the titanium plate substrate, polishing the titanium plate substrate with 45 mesh white corundum in turn, soaking in a sodium hydroxide aqueous solution with a mass concentration of 32% at 55°C for 1.1 hours, rinsing with desalted water to neutrality, soaking in a sulfuric acid aqueous solution with a mass concentration of 22% at 55°C for 1.2 hours, rinsing with desalted water to neutrality, and storing in a nitrogen atmosphere to obtain the pretreated titanium plate substrate. Step II, preparing the dipping solution, firstly mixing citric acid and ethylene glycol in a molar ratio of 1:5.0, and reacting at 65°C for 1.2 hours to obtain a citrate ethylene glycol solution; then mixing the citrate ethylene glycol solution, tin chloride pentahydrate, antimony trichloride, and copper nitrate trihydrate, by mass, 1000 parts: (95 parts): (3 parts): (0.7 parts) for 0.6 hours to obtain a coating dipping solution. Step III, apply 220 ml of the scraper coating per square meter of the titanium plate substrate in a nitrogen atmosphere to obtain a scraper-coated wet plate; the above-mentioned scraper-coated wet plate is dried in a nitrogen drying oven at 145kPaG and 145°C for 0.6 hours to obtain a scraper-coated dry substrate; Step IV, the above-mentioned scraper-coated dry substrate is roasted in an air roasting furnace at 145kPaG and 515°C for 15 minutes, and then naturally cooled to room temperature to obtain a scraper-coated roasted substrate; repeat steps III and IV for 11 times, and for the last roasting, control the roasting time to be 1.3 hours in an air roasting furnace at 145kPaG and 515°C to obtain a titanium-based coating electrode modified with tin, antimony and copper.

[0140] In step S3, the electro-oxidation reactor is composed of a first-stage electro-oxidation reactor, a second-stage electro-oxidation reactor, and a third-stage electro-oxidation reactor. The electrode size in the electro-oxidation reactor is (2.1 meters) × (4.2 meters), the electrode spacing is 2.5 centimeters, the cathode is a titanium mesh, and the anode is the above-mentioned titanium-based coating electrode modified with tin, antimony, and copper. The electrolyte of the electro-oxidation reactor, in terms of mass concentration, has a mass concentration of sodium sulfate and sodium chloride of 3.5% and 1%, respectively, and the rest is desalted water. The linear velocity of the electrolyte on the electrode surface is 0.6 meters per second. The voltage of the first-stage electro-oxidation reactor is 1.3 volts, the current density is 35 milliamperes per square centimeter, the operating pressure is 0.6 MPaG, and the operating temperature is 21°C. The voltage of the second-stage electro-oxidation reactor is 1.3 volts, the current density is 16 milliamperes per square centimeter, the operating pressure is 0.6 MPaG, and the operating temperature is 21°C. The third-stage electro-oxidation reactor has a voltage of 1.3 V, a current density of 8 mA / cm2, an operating pressure of 0.6 MPaG, and an operating temperature of 21° C. The chlorine content in the ammonia stripping lean solution after regeneration reaches 0.7 ppm, and the ammonia content reaches 2.2 ppm.

[0141] The ammonia content in the deammoniation washing liquid obtained in step S2 is 8 ppm. The ammonia content in the deammoniation purified gas obtained in step S1 is 4.7 ppm, which can meet the feed requirements of the subsequent processing technology.

[0142] [Example 4]

[0143] The separation process for the raw gas in this embodiment is the same as that in embodiment 2. The only difference between this embodiment and embodiment 2 is that the raw gas used in this embodiment comes from a different refinery gas source. The raw gas composition, by volume ratio, includes: methane 18.4280%, ethane 7.6138%, ethylene 16.0519%, propane 0.1725%, propylene 0.8638%, isobutane 0.0810%, n-butane 0.0163%, trans-butene 0.0069%, n-butene 0.0192%, isobutene 0.0377%, cis-butene 0.0002%, oxygen 0.1334%, nitrogen 13.2409%, hydrogen 29.9967%, carbon monoxide 1.5357%, carbon dioxide 3.2119%, acetylene 0.0055%, 1,3-butadiene 0.0001%, hydrogen sulfide 6.5248%, alkanes or alkenes with a carbon content of more than five carbon atoms 1.1821%, ammonia 0.0113%, and other components 0.8664%.

[0144] The ammonia content in the deammoniation aqueous solution obtained in step S2 is 1 ppm. The ammonia content in the deammoniation purified gas obtained in step S1 is 0.1 ppm, which can meet the feed requirements of the subsequent processing technology.

[0145] [Example 5]

[0146] The separation process for the raw gas in this embodiment is the same as that in embodiment 2. The only difference between this embodiment and embodiment 2 is that the raw gas used in this embodiment comes from a different refinery gas source. The raw gas composition, by volume ratio, includes: methane 16.8604%, ethane 8.3524%, ethylene 17.3045%, propane 0.1764%, propylene 0.8117%, isobutane 0.0763%, n-butane 0.0165%, trans-butene 0.0071%, n-butene 0.0179%, isobutene 0.0361%, cis-butene 0.0002%, oxygen 0.1372%, nitrogen 13.6905%, hydrogen 27.9388%, carbon monoxide 1.5623%, carbon dioxide 3.4286%, acetylene 0.0053%, 1,3-butadiene 0.0001%, hydrogen sulfide 7.1986%, alkanes or alkenes with a carbon content of more than five carbon atoms 1.2924%, ammonia 0.1087%, and other components 0.9780%.

[0147] The ammonia content in the deammoniation aqueous solution obtained in step S2 is 9 ppm. The ammonia content in the deammoniation purified gas obtained in step S1 is 4.8 ppm, which can meet the feed requirements of the subsequent processing technology.

[0148] [Example 6]

[0149] The only difference between this embodiment and embodiment 2 is the raw gas. The raw gas described in this embodiment is derived from coke oven gas, and the composition, by volume ratio, includes:

[0150] Carbon monoxide 5.3%, hydrogen 56.1%, methane 22.6%, (C2-C5) hydrocarbons 2.2%, oxygen 0.9%, nitrogen 8.4%, carbon dioxide 1.8%, ammonia 0.0430%, and other components 2.6%.

[0151] The ammonia content in the deammoniation washing liquid obtained in step S2 is 2.4 ppm. The ammonia content in the deammoniation purified gas obtained in step S1 is 0.95 ppm, which can meet the feed requirements of the subsequent processing technology.

[0152] [Example 7]

[0153] The only difference between this embodiment and embodiment 2 is the raw gas. The raw gas described in this embodiment is derived from the producer gas, and the composition is calculated by volume ratio, including:

[0154] Carbon monoxide 26.2%, hydrogen 14.3%, methane 1.4%, (C2-C5) hydrocarbons 0.3%, oxygen 0.2%, nitrogen 49.5%, carbon dioxide 4.6%, ammonia 0.0620%, and other components 3.4%.

[0155] The ammonia content in the deammoniation washing liquid obtained in step S2 is 3.4 ppm. The ammonia content in the deammoniation purified gas obtained in step S1 is 1.3 ppm, which can meet the feed requirements of the subsequent processing technology.

[0156] [Example 8]

[0157] This embodiment is different from the embodiment 2 only in the raw gas. The raw gas described in this embodiment is derived from heavy oil cracking gas, and the composition is calculated by volume ratio, including:

[0158] Carbon monoxide 1.5%, hydrogen 18.7%, methane 39.8%, (C2-C5) hydrocarbons 35.3%, oxygen 0.3%, nitrogen 2.1%, carbon dioxide 0.4%, ammonia 0.0710%, and other components 1.8%.

[0159] The ammonia content in the deammoniation washing liquid obtained in step S2 is 3.9 ppm. The ammonia content in the deammoniation purified gas obtained in step S1 is 1.6 ppm, which can meet the feed requirements of the subsequent processing technology.

[0160] [Example 9]

[0161] This embodiment is different from the embodiment 2 only in the raw gas. The raw gas described in this embodiment is derived from natural gas, and the composition is calculated by volume ratio, including:

[0162] Methane 71.8%, (C2-C5) hydrocarbons 15.2%, nitrogen 7.9%, carbon dioxide 2.3%, ammonia 0.0650%, and other components 2.7%.

[0163] The ammonia content in the deammoniation washing liquid obtained in step S2 is 3.6 ppm. The ammonia content in the deammoniation purified gas obtained in step S1 is 1.5 ppm, which can meet the feed requirements of the subsequent processing technology.

[0164] [Example 10]

[0165] The only difference between this embodiment and embodiment 2 is the raw gas. The raw gas described in this embodiment is derived from the anaerobic fermentation gas of organic matter, and the composition is calculated by volume ratio, including:

[0166] Carbon monoxide 0.4%, methane 68.9%, (C2-C5) hydrocarbons 0.9%, nitrogen 0.8%, carbon dioxide 27.3%, ammonia 0.0380%, and other components 1.6%.

[0167] The ammonia content in the deammoniation water washing liquid obtained in step S2 is 2.1 ppm. The ammonia content in the deammoniation purified gas obtained in step S1 is 0.83 ppm, which can meet the feed requirements of the subsequent processing technology.

[0168] [Comparative Example 1]

[0169] The raw gas used in this comparative example is the same as that in Example 3, and the alkaline impurities are removed by water washing in a packed tower. The equipment and process operating conditions of the water washing tower are as follows: the temperature is 35°C, the pressure (gauge pressure) is 1000kPa, the theoretical plate number is 18, the dilute phosphoric acid aqueous solution with a pH of 3 is used, and the gas-liquid volume ratio is 40.

[0170] The volume content of ammonia in the obtained ammonia-purified gas was 82 ppm.

[0171] [Comparative Example 2]

[0172] This comparative example uses commercial SQD-67 resin (H type) (Suqing Resin Company) as the adsorbent and adopts a conventional fixed bed adsorption process. The adsorption conditions are as follows: the resin filling volume is 500 cubic meters, the adsorption temperature is 30°C, and the volume space velocity is 50h -1 .

[0173] The raw gas is the same as that in Example 3. In the initial stage of operation, the volume content of ammonia in the obtained propylene-removed purified gas is 4 ppm, and the adsorbent breaks through after about 9 days, requiring 4% to 6% sulfuric acid for regeneration, and the volume consumption of the regeneration liquid per unit volume of the adsorbent is 4 to 5 times.

[0174] The above describes the specific implementation of the present invention in detail, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the various technical features being combined in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A modified hollow fiber membrane, characterized in that: The modified hollow fiber membrane comprises a base membrane, a graft layer and an outer wall, wherein the graft layer is coated on the inner surface of the base membrane, and the outer wall is coated on the outer surface of the base membrane; the base membrane is a modified base membrane containing sulfonic acid groups and carboxyl groups, wherein the carboxyl content in the base membrane is 3.8 to 11.2 mmol / g, and the sulfonic acid content is 1.9 to 8.4 mmol / g; the graft layer is a graft layer containing carboxyl groups and sulfonic acid groups, wherein the carboxyl content in the graft layer is 14.4 to 32.4 mmol / g, and the sulfonic acid content is 7.2 to 24.3 mmol / g; the outer wall is a polydimethylsiloxane layer with a thickness of 80 to 160 microns; the viscosity of the polydimethylsiloxane is 5000 to 10000 centipoise.

2. The modified hollow fiber membrane according to claim 1, characterized in that: The inner diameter of the modified hollow fiber is 0.3-1.0 mm, and / or the thickness of the base membrane is 0.4-1.5 mm.

3. The modified hollow fiber membrane according to claim 1, characterized in that: The base film is a polypropylene film modified by a first modifier; the first modifier is sodium poly(4-styrenesulfonic acid-co-maleic acid) and sodium polyanisenesulfonate, and the mass ratio of sodium poly(4-styrenesulfonic acid-co-maleic acid) to sodium polyanisenesulfonate is (8-15):(2-6).

4. The modified hollow fiber membrane according to claim 3, characterized in that: The molecular weight of the sodium poly(4-styrenesulfonic acid-co-maleic acid) is 4000-7000, and the molecular weight of the sodium polyanisyl sulfonate is 6000-10000.

5. The modified hollow fiber membrane according to claim 3, characterized in that: The molecular weight of the polypropylene is 40,000-50,000.

6. The method for preparing the modified hollow fiber membrane according to claim 1 or 2, comprising: (1) preparing a basement membrane; (2) coating the inner surface of the base film with a grafted layer; (3) Then, an outer wall is coated on the outer surface of the base membrane to obtain a modified hollow fiber membrane.

7. The preparation method according to claim 6, characterized in that: The method for preparing the modified hollow fiber membrane comprises: (1) preparing a casting solution containing a first modifier, a core solution and an outer gel bath, and then forming the hollow fiber membrane by hollow fiber spinning and drying, thereby obtaining a hollow fiber membrane, i.e., a base membrane; (2) Swelling the hollow fiber membrane, treating it with a second modifier, and treating it with a third modifier to form a graft layer; (3) The hollow fiber membrane covered with the grafted layer obtained in step (2) is subjected to a third post-modification treatment to cover the hollow fiber membrane with a polydimethylsiloxane layer.

8. The preparation method according to claim 7, characterized in that: The first modifier described in step (1) is sodium poly(4-styrenesulfonic acid-co-maleic acid) and sodium polyanisyl sulfonate, and the mass ratio of sodium poly(4-styrenesulfonic acid-co-maleic acid) to sodium polyanisyl sulfonate is (8-15):(2-6).

9. The preparation method according to claim 8, characterized in that: The molecular weight of sodium poly(4-styrenesulfonic acid-co-maleic acid) is 4000-7000, and the molecular weight of sodium polyanisyl sulfonate is 6000-10000.

10. The preparation method according to claim 7 or 8, characterized in that: The casting liquid containing the first modifier in step (1) comprises: polypropylene, N-methylpyrrolidone, diethylene glycol, and the first modifier, wherein the mass ratio of polypropylene, N-methylpyrrolidone, diethylene glycol, and the first modifier is (20-30): (100-150): (2-6): (10-20); the core liquid is an N-methylpyrrolidone solution, wherein the mass concentration of the N-methylpyrrolidone solution is 2% to 8%.

11. The preparation method according to claim 10, characterized in that: The molecular weight of polypropylene is 40,000 to 50,000.

12. The preparation method according to claim 7, characterized in that: The swelling agent used in step (2) is selected from at least one of toluene, p-xylene, m-xylene and o-xylene, the swelling temperature is 80-120° C., the swelling time is 5-12 hours, and the volume ratio of the swelling agent to the hollow fiber membrane is 2-5; And / or, the second modifier in step (2) is a second modifying component, a catalyst and a solvent; the catalyst is selected from one of a Lewis acid or a Lewis base; the solvent is selected from at least one of toluene, p-xylene, m-xylene and o-xylene; And / or, the treatment conditions of the treatment with the second modifier are as follows: the second modifier passes through the inner cavity of the hollow fiber membrane, the flow line velocity is 0.2 m / s to 0.5 m / s, the treatment temperature is 30°C to 60°C, and the treatment time is 20 to 40 minutes.

13. The preparation method according to claim 12, characterized in that: The second modifying component is at least one selected from 1,3,5-tris[4-(chloromethyl)phenyl]benzene, 1,3,5-trichlorobenzene, and 1,3,5-tris(chloromethyl)benzene.

14. The preparation method according to claim 12, characterized in that: In step (2), the catalyst is at least one of anhydrous zinc chloride, anhydrous tin tetrachloride, and anhydrous aluminum chloride.

15. The preparation method according to claim 12, characterized in that: In step (2), the second modified component: catalyst: solvent = (5-15): (1-3): (100-200) in parts by mass.

16. The preparation method according to claim 7, characterized in that: The third modifier is a third modifying component, sodium hydroxide and a solvent; the solvent is selected from at least one of toluene, p-xylene, m-xylene and o-xylene; And / or, the treatment conditions of the third modifier treatment are as follows: the third modifier passes through the inner cavity of the hollow fiber membrane, the flow line velocity is 0.2 m / s to 0.5 m / s, the treatment temperature is 40°C to 80°C, and the treatment time is 5 to 15 minutes.

17. The preparation method according to claim 16, characterized in that: The third modifying component is selected from at least one of N-(carboxymethyl)maleamic acid, 3,4,5-tricarboxylic acid aniline, and 5-(3,5-dicarboxybenzamido)isophthalic acid.

18. The preparation method according to claim 16, characterized in that: Calculated by mass, the third modifying component: sodium hydroxide: solvent = (5-15): (1-3): (100-200).

19. The preparation method according to claim 7, characterized in that: The post-treatment agent used in the third modification post-treatment is a polydimethylsiloxane solution with a mass concentration of 2% to 6%, and the solvent is selected from at least one of toluene, p-xylene, m-xylene, and o-xylene; the outer wall of the modified hollow fiber membrane obtained by the third modification post-treatment is polydimethylsiloxane with a thickness of 80 to 160 microns.

20. Use of the modified hollow fiber membrane according to any one of claims 1 to 5 or the modified hollow fiber membrane prepared by the preparation method according to any one of claims 6 to 19 in a process for deammoniation of ammonia-containing gas.

21. The use according to claim 20, characterized in that The deammoniation process is a water-washing deammoniation process, and the application is to use the modified hollow fiber membrane as a membrane extraction component to perform back extraction on ammonia-containing water washing liquid.